The Pesantren (Islamic Boarding School) Tradition in Preparing Human Resources at Pesantren Darul Hijrah Banjarbaru, Pesantren Ibnul Amin Pamangkih, and Pesantren Rasyidiyah Khalidiyah Amuntai in South Kalimantan Province - Yuseran, Muhammad; Muharramah, Nauriatul (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This pesantren education model not only maintains its existence, but it also significantly contributes to the advancement of science. Within the world of pesantren, there is a term known as pesantren tradition. Pesantren tradition is defined as the habits practiced by pesantren residents. Therefore, to envision the future of pesantren education and its potential to play a strategic role and be considered an option, it is essential to possess open-mindedness and courage to address its challenges fundamentally and comprehensively. One approach to achieving this is by cultivating habits and traditions within pesantren. The results have shown that several traditions have developed in the boarding schools studied by the author, which are related to both scientific and skill-based fields. In science, these traditions include writing books, practicing reading the yellow book, following the rules of learning Nahwu and Sharaf, and fostering the habit of memorizing vocabulary (in Arabic and English). In the field of skills, there are traditions such as engaging in foreign language conversations (in Arabic and English), reading maulid, observing the pilgrimage tradition, participating in muhadharah/foreign language speech practice (in Arabic, English, and Indonesian), adhering to the rules of memorizing the Qur'an, memorizing prayers for the deceased, conducting haul prayers and congratulatory prayers, upholding haulan traditions, and practicing khat/calligraphy.